2009
DOI: 10.1080/10236240903454202
|View full text |Cite
|
Sign up to set email alerts
|

Cues from the predator crabThalamita danaefed different prey can affect scope for growth in the prey musselPerna viridis

Abstract: Clearance rate (CR), absorption efficiency (AE), respiration rate, excretion rate and scope for growth (SFG) were investigated in the green-lipped mussel Perna viridis upon exposure to predatory crabs, Thalamita danae, that had been either starved or maintained on diets with P. viridis or shrimp tissue. The CR and SFG were significantly lower when the mussels were exposed to starved T. danae or those fed with mussels. The differences were observed immediately after the mussels were exposed to the cues (Day 0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
(71 reference statements)
0
12
1
Order By: Relevance
“…Several laboratory studies have shown that prey can assess and respond to varying predation risks according to whether the predator feeds on alternative prey (e.g. Hagen et al 2002, Shin et al 2009, Bourdeau 2010. Our results suggest that under natural conditions of multiple cues and risks, this fine assessment may not be possible or effective in these 4 grazer species.…”
Section: Discussioncontrasting
confidence: 46%
“…Several laboratory studies have shown that prey can assess and respond to varying predation risks according to whether the predator feeds on alternative prey (e.g. Hagen et al 2002, Shin et al 2009, Bourdeau 2010. Our results suggest that under natural conditions of multiple cues and risks, this fine assessment may not be possible or effective in these 4 grazer species.…”
Section: Discussioncontrasting
confidence: 46%
“…They may build a stronger shell as protection from crushing consumers like crabs (Micheli 1995, Leonard et al 1999, Nakaoka 2000. Mussels exhibit additional morphological defenses against predators including producing extra byssal threads to more firmly attach themselves to the substrate (Cote 1995, Leonard et al 1999, Shin et al 2009) and/or grow thicker abductor muscles to discourage prying predators (Freeman 2007, Freeman et al 2009). Some bivalves reduce predation risk by reducing their feeding rates to minimize release of cues that attract predators (Smee & Weissburg 2006, Naddafi et al 2007, while others burrow more deeply to escape from burrowing consumers (Griffiths & Richardson 2006, Flynn & Smee 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing shell thickness in the presence of crushing predators (crabs), mussels (Mytilus edulis) also increased byssal thread production to increase the force needed by predators to remove them from hard substrates (Cote 1995, Leonard et al 1999, Shin et al 2009) and to increase abductor muscle mass for some predators (whelks) (Freeman 2007, Freeman et al 2009). Hard clams Mercenaria mercenaria grow more slowly in the presence of knobbed whelk Busycon carica predators (Nakaoka 2000), possibly because they reduce their feeding (pumping) time in response to them (Irlandi & Peterson 1991, Smee & Weissburg 2006.…”
Section: Introductionmentioning
confidence: 99%
“…They respond to risk by increasing their burrowing depth (Griffiths & Richardson 2006, Flynn & Smee 2010, reducing their feeding behavior (Smee & Weissburg 2006a,b, Naddafi et al 2007, and increasing their shell thickness (Trussell & Smith 2000, Caro & Castilla 2004, Freeman & Byers 2006. Additionally, mussels produce additional byssal threads to in crease the force needed to dislodge them from substrates (Coté 1995, Leonard et al 1999, Shin et al 2009) and increase abductor muscle mass to deter prying predators (Freeman & Byers 2006). Morphological changes in shell thickness are a trade-off with soft tissue mass and gonad size, and thus increasing shell thickness may lower bivalve fecundity (Peterson 1986).…”
Section: Introductionmentioning
confidence: 99%